EFEKTIVITAS LEMBAGA KESWADAYAAN MASYARAKAT (LKM) DALAM PENGENTASAN KAWASAN KUMUH DI KECAMATAN RUMBAI KOTA PEKANBARU - Putri, Lusi Dwi; nasution, sri roserdevi; harsini, harsini (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2018)
LKM is the spearhead of the success of slums in urban poverty alleviation programs, especially in the area of Sri Meranti Village, Rumbai, Pekanbaru. This study aims to determine the performance of the LKM in Sri Meranti Village, Rumbai, Pekanbaru.. The assessment takes place in 2018 (2017 performance audit) by comparing with secondary data that has been obtained in the LKM performance assessment results at the end of 2015 and the end of 2016. Qualitative research is the method chosen in this study. Data retrieval is done using primary data and secondary data related to the results of LKM performance appraisal compared during the last 3 (three) years work process. Data collection techniques are interviews, direct observation to the field and document review